Pengaruh Penerapan Penelaahan Alkitab (PA) terhadap Moral Pemuda-Pemudi Di GKPI Simpang Tiga Bahalimbalo Resort Paranginan Tahun 2022 - Martin Tambunan; Bernhardt Siburian; Bestian Simangunsong (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The purpose of this study is to determine whether the implementation of this Bible study has a positive and significant influence on the morals of the young men and women of GKPI Simpang Tiga Bahalimbalo, Paranginan Resort in 2022. The method used in this study is a quantitative research method. The population in this study were all young men and women at GKPI Simpang Tiga Bahalimbalo, Paranginan Resort in 2022 with a total of 52 people. Data were collected with a closed questionnaire of 30 items. The results of the data analysis show that there is an influence of the application of Bible study (PA) on the morals of young men and women at the GKPI Simpang Tiga Bahalimbalo Resort Paranginan in 2022: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.563> rtable ( = 0.05, n = 52) = 0.297 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value = 4.819> ttable ( = 0.05, dk = n-2 = 50) = 2.000 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂=